2008
DOI: 10.1111/j.1551-2916.2008.02396.x
|View full text |Cite
|
Sign up to set email alerts
|

Mixed‐Valence Perovskite Thin Films by Polymer‐Assisted Deposition

Abstract: In thin films of rare‐earth manganites, RE1−xMxMnO3 (RE=rare earth, M=Ca, Sr, Ba), with mixed‐valence perovskite structure, the transport properties highly depend on the deposition technique, processing conditions, and the substrate used. Chemical solution deposition techniques provide many advantages, such as low cost, easy setup, and coating of large areas. However, the crystalline quality, uniformity, and reproducibility of the film depend on the reactivity of the chemical used for solution preparation. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Among CSD techniques, we selected polymerassisted deposition (PAD) [31][32][33] because it is one of the most suitable processes to produce high-quality epitaxial complex and multilayer structured films [34]. In particular, high-quality epitaxial LSMO thin films were synthetized on single crystal-substrates by PAD [35,36] with a perfect control of the thickness [37] to prepare multilayers controlling their magnetoresistive response [38] and tunnel junctions [39]. PAD is a softchemistry technique that uses branched polymers to coordinate and stabilize different cations in an aqueous solution, which is therefore homogeneously spin-coated on a substrate [40].…”
Section: Introductionmentioning
confidence: 99%
“…Among CSD techniques, we selected polymerassisted deposition (PAD) [31][32][33] because it is one of the most suitable processes to produce high-quality epitaxial complex and multilayer structured films [34]. In particular, high-quality epitaxial LSMO thin films were synthetized on single crystal-substrates by PAD [35,36] with a perfect control of the thickness [37] to prepare multilayers controlling their magnetoresistive response [38] and tunnel junctions [39]. PAD is a softchemistry technique that uses branched polymers to coordinate and stabilize different cations in an aqueous solution, which is therefore homogeneously spin-coated on a substrate [40].…”
Section: Introductionmentioning
confidence: 99%
“…Hole‐doped pervoskite manganites such as La 1‐x Sr x MnO 3 (LSMO) have been of great interest due to their complex magneotransport properties. In these manganites intrinsic colossal magnetoresistance (CMR), which is a gigantic decrease of resistance by the application of an external magnetic field, is observed near the Curie temperature ( T c ) with high applied magnetic fields (≥1 T) 1–3. Recently, there has been considerable research in order to achieve high magnetoresistance (MR) values with lower magnitude of the applied magnetic fields (<1 T) by taking the advantage of the extrinsic MR effect 4–6.…”
Section: Introductionmentioning
confidence: 99%
“…3 Jia et al suggested a polymer-assisted deposition (PAD) method, where the addition of organic polymers such as poly(ethyleneimine) (PEI) with ethylenediaminetetraacetic acid (EDTA) prevents the metal ions from engaging in unwanted chemical reactions, and maintains the desired viscosity of solutions for controlling lm thickness, resulting in the deposition of metal oxide lms from aqueous solutions. [4][5][6][7][8][9][10][11][12][13] These synthetic routes assisted by organic polymers would allow us to achieve many kinds of metal oxide lms from aqueous solutions of metal salts.…”
mentioning
confidence: 99%